DVPOSitive: Effective Sales Application and Smart Stock for DistributorCompanies PT Indofood Sukses Makmur Tbk Based on Microsoft Access - Nurnajmi, Difa Nasywa; Nisanur, Visi Aulia (Ebiz Prima Nusa, 2025)
This project activity is carried out to create an applicationthat can help the sales process and stock management ofgoods more easily, quickly, and regularly. This application isbuilt using Microsoft Access because it is easy to use andsuitable for small business needs. In applicationdevelopment, database design, input and output forms arecreated, and automatic report preparation is carried out. Theapp can record purchase and sale transactions, monitor stockof goods directly, and present reports needed by users. Theresults of using this application show that the transactionrecording process becomes faster and errors in stockmanagement can be reduced. With this application, the salesprocess becomes more efficient and effective. Thisapplication is suitable for business actors who want to startusing digital systems without having to use complicated orexpensive applications.